(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The extent to which people are happy in their jobs affects many areas of their lives, including their mental health, career choices, and level of education. Many studies have shown a positive relationship between job happiness and educational achievement. This means that those who enjoy their work more are likely to have more degrees or specialized skills. When people are happy in their jobs, they are more likely to pursue occupations that reflect their interests and beliefs, which in turn makes them more invested in their work and more productive. Negative effects on mental health, including anxiety, sadness, and burnout, have been associated with dissatisfaction with one’s employment. A healthier and more satisfying workforce can only be achieved by gaining a deeper knowledge of the interplay between job satisfaction and factors including educational achievement, professional choices, and mental health.